Map of Tourism Village Management in Kudus Regency, Central Java - Istriyani, Ratna (Asketik: Jurnal Agama dan Perubahan Sosial, 2024)
This research examine the pioneering process of tourist villages in Kudus, by looking at management and capital that influence tourism development. This research used qualitative approach, with purposive sampling to determine research object and informants by looking at the criteria for 3 sub-districts that have the highest number of tourist villages. Researchers interviewed pioneer actors and tourism village managers and the surrounding community, supported by observational data. The results of this research show that there were differences and disparity in the development of tourist villages in North Kudus and South Kudus. It can be seen from the history of the establishment of tourism and management. The tourist village in North Kudus appears sporadically because there are quite a lot of private parties. This influences the management strategy which is investor-based with the support of financial capital and the sensitivity of actors (investors) in capturing natural potential and visiting opportunities (production center development). It was different from the Tourism Village in South Kudus which historically emerged because of collective awareness (social capital) to develop social activism and economic opportunities through tourism villages. Therefore managing natural and cultural potential carried out collectively by empowering local communities (people center development).